A distributed architecture for policy-customisable multi-tenant processes-as-a-service. Issue 4 (3rd July 2016) - Wang, MingXue; Bandara, Kosala Yapa; Pahl, Claus
Abstract : Service-based business processes are often developed and deployed by single organisations. In distributed, shared resource environments like the cloud on the other hand, consumers share resources owned by cloud providers. This requires multi-tenancy capability for service processes that provide customised behaviour on shared process implementations to meet the varying needs of different process consumers as tenants of the process resource. In this paper, we define a distributed multi-tenant architecture for Business Process Execution Language (BPEL) processes provided as a service. A single-version BPEL process is deployed by a provider and offered for all process consumers, combined with a customisation and management functionality to create a unique experience for different consumers (process tenants). We provide two core components: a policy model for consumers to express customisation/business requirements of service processes and a coordination framework for policy enforcement between consumers and providers to achieve on-the-fly customisation of service processes.